2019
DOI: 10.1016/j.quageo.2018.04.012
|View full text |Cite
|
Sign up to set email alerts
|

OSL surface exposure dating of a lithic quarry in Tibet: Laboratory validation and application

Abstract: A B S T R A C TRecent work has shown that the optically stimulated luminescence (OSL) signal can be used to determine the duration of daylight exposure for rock surfaces, complementing the surface exposure dating technique using cosmogenic nuclides. In this study we investigate the feasibility of using the newly developed OSL Surface exposure dating technique (OSL-Surf) to date flake scars at lithic quarry sites. We performed the first quantitative validation of the model describing the OSL-Surf dating techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 19 publications
1
58
0
Order By: Relevance
“…Other studies have reported similar observation of bleaching to depths >20 mm (e.g. Sohbati et al 2012;Ou et al 2018;Gliganic et al 2019), although these were usually observed in visibly translucent samples, such as quartzite.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Other studies have reported similar observation of bleaching to depths >20 mm (e.g. Sohbati et al 2012;Ou et al 2018;Gliganic et al 2019), although these were usually observed in visibly translucent samples, such as quartzite.…”
Section: Discussionsupporting
confidence: 51%
“…; Gliganic et al . ), although these were usually observed in visibly translucent samples, such as quartzite.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the attenuation coefficients are different according the energy of stimulation (e.g., IRSL measured at 50 °C and the post-IR IRSL signal measured at 225 °C). Meyer et al (2018) and Gliganic et al (2018) have shown that the distribution of opaque minerals between rock slices can significantly affect the reproducibility of luminescence-depth profiles. They conclude the need for close petrographic analysis of luminescence-depth profile samples to ensure that the rock cores from calibration and application sites have a similar 5 mineralogical composition and therefore share similar µ parameter.…”
Section: Osl Surface Exposure Dating 211 the Bleaching Modelmentioning
confidence: 99%
“…Luminescence dating is based on the accumulation of trapped electrons through time in the crystalline lattice of specific minerals (e.g., quartz or feldspar), which are sensitive to daylight (Aitken, 1985;Huntley et al, 1985). In addition to its 30 common application to date sediment burial in a range of geomorphological environments (e.g., Duller, 2008;Rhodes, 2011;Fuchs and Owen, 2008), luminescence dating can also be used to determine the exposure of both naturally formed and anthropogenically formed rock surfaces (e.g., Polikreti et al, 2003;Sohbati et al, 2011;Gliganic et al, 2018;Lehmann et al, 2018). This latter application is based on the principle that when a rock surface is exposed to daylight, the luminescence signal, Earth Surf.…”
mentioning
confidence: 99%
See 1 more Smart Citation